Using properties of determinant prove that `|[1, a, a^2],[1, b, b^2],[1, c, c^2]| = (a-b)(b-c)(c-a)`

Expert Answers

An illustration of the letter 'A' in a speech bubbles

The determinant of a matrix ` [[a, b, c],[d,e,f],[g,h,i]]` is given by:

`|[a, b, c],[d,e,f],[g,h,i]|`= `a*(e*i - f*g) - b*(d*i - g*f) + c*(d*h -e*g)`

The determinant that has to be found `|[1, a, a^2], [1, b, b^2],[1, c, c^2]|`

= `1*(b*c^2 - b^2*c) - a*(c^2 - b^2) + a^2*(c - b)`

=> `b*c^2 - b^2*c + a*b^2 - a*c^2 + a^2*c - a^2*b`

=> `bc(c - b) + a(b - c)(b + c) + a^2(c - b)`

=> `(b - c)(ab + ac - bc - a^2)`

=> `(b - c)(a(c - a) -b(c - a))`

=> `(a - b)(b - c)(c - a)`

This proves that `|[1, a, a^2], [1, b, b^2],[1, c, c^2]|` = `(a - b)(b - c)(c - a)`

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial